1146 Interaction Of Mild Cognitive Impairment And Late-life Depression In Actigraphy And Self Report Of Sleep Problems. (27th May 2020) - Aronis, J; Daigle, K; Almaghasilah, A; Gilbert, C; Fremouw, T; Singer, C; Abedi, A; Hayes, M
Abstract: Introduction: Late-life depression has been proposed as a precursor to amnestic Mild Cognitive Impairment (aMCI), the prodrome of Alzheimer's disease. Both conditions are associated with sleep and cognitive problems. We hypothesized that MCI and current depressive symptoms would co-occur more frequently, but express distinct sleep phenotypes. Methods: Independently living older adults (N=80), age 62-90 (M=71.78, SD=5.98), were recruited from a geriatric psychiatry clinic and the community for a home sleep study. A clinical decision board and neurocognitive battery were used to determine MCI status. Participants completed the CES-D and depression history interview where endorsement of current depression was considered positive. Sleep was examined with wrist actigraphy for 7 days. Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Stanford Sleepiness Scale (SSS) provided subjective sleep quality. Results: Based on these criteria, 41.2% of the sample were determined to be MCI (n=33); the remainder were deemed normative for age (NC; n=47). Chi-square analyses showed a higher frequency of MCI were positive for current depression than expected (14.2%; p=0.017). Repeated-measures MANOVA, using current depression symptoms and MCI as factors, revealed MCI was associated with longer sleep latency (p=0.035) and wake bout time (p=0.039); whereas, current depression was associated with longer sleep latency, more fragmentation/WASO, and lower sleep efficiency (p's<0.05), self-report of poorer daytime dysfunction (p=0.005), and greater daytime sleepiness (p=0.001). MCI x current depression interactions were found for sleep latency (p=0.029); and PSQI sleep disturbances (p=0.005) and sleep medication (p=0.025). Conclusion: Despite distinct sleep disordered phenotypes, the interaction of MCI and current depression is associated with delayed sleep onset, use sleep medication and report of sleep disturbances. Support: This project was sponsored by: NASA, Maine Space Consortium; AG 056176, AG 053164 Vice President for Research, U. Maine; Maine Technology Institute; DoD Phase I SBIR and R44AG059536-01 SBIR Phase II Award.